Multiple sclerosis in Australia: socioeconomic factors. Issue 3 (September 1996) - Hammond, S R; McLeod, J G; Macaskill, P; English, D R
Abstract : The data from an epidemiological study on multiple sclerosis in Australia have been analysed to determine the relation between the prevalence of the disease and educational level, and the association between level of disability and employment status. There was a significantly higher frequency of multiple sclerosis in those who left school at an older age and achieved a higher educational level. The explanation of this finding remains speculative and may be related to genetic or environmental factors. The study confirmed the recognised association between moderate-severe disability and divorce-separation and lower rates of employment.